Rare manifestation of Neurofibromatosis type 1: A plexiform neurofibroma involving the mediastinum and lungs with endobronchial neurofibromata. Issue 1 (20th September 2018) - Pascoe, Heather M; Antippa, Phillip; Irving, Louis; Christie, Michael; McCusker, Mark W
Summary: Neurofibromatosis type 1 (NF1) is a multisystem phakomatosis. The intrathoracic manifestations of NF1 are protean. We describe a rare case of a plexiform neurofibroma infiltrating the mediastinum and lungs with multiple endobronchial neurofibromata. To our knowledge, a mediastinal plexiform neurofibroma extending into the lungs on CT has not been reported.